Acklen family log cabin on the Klondike River, Dawson, Yukon Territory, approximately 1899. - Hegg, Eric A., 1867-1948 (1899)
Possibly members of the Acklen family standing in the foreground. Caption on image: "Acklen Villa on the Klondyke River. Dawson Y.T." Original photograph by Eric A. Hegg 139; copied by Webster and Stevens 109.A. Klondike Gold Rush.